The assessment of light pollution in the city of Kyiv - Radomska, Margaryta; Kovalska, Victoria; Oyewole, Grace Titilope (Видавництво Львівської політехніки, 2021)
The analysis of environmental issues raised by the excessive artificial illumination in the selected areas of the central districts of Kyiv was conducted. The level of light pollution was measured using photometric equipment and compared to the levels of natural illumination. The instrumental measurements were amended with visual observation of sky glow levels and subjective perception of sunset timing. Based on the obtained results the possible health effects for the residents of affected districts were considered.
Keywords: light pollution; health effects; stellar visibility; photometry; Bortle scale